Empowering Science Students with the Production of Oil from Watermelon Seed and its Importance Using Sohlex Extractor - Falilat, Olawuwo Adeboola; Taiwo, O. Dahunsi (International Journal of Recent Advances in Multidisciplinary Topics, 2023)
The paper examined the processes involved in the production of oil from watermelons seed and its importance using sohlex extractor where N-hexane (Cyclohexane) was used as a solvent. Different variables of watermelons seeds were considered in term of particle sizes, ratio of solvent to seeds mass and quantity of oils that could produce from the process. The nutritional value of the oils and phytochemical analysis of the oil produced was carried out to determine if it’s fit for human consumption, oil content, Fatty acid composition and Modification in watermelons seed oils were also examined. The findings revealed that the watermelon seed oils contain minerals salts such as Calcium, Phosphorous, Magnesium and Potassium in large amounts and it also contain vitamins such as Niacin, Thiamin, Riboflavin and vitamin B-6. Watermelons oil has some health benefits such as antioxidant against cancer. Can reduce cholesterol, high protein in vegetarian diet. Due to certain challenges identified from production processes some recommendations were made: government should encourage the science graduate to go into watermelon production by empowering them, make loan facility available, the research institutes should make public awareness on the health benefits of watermelon seed oils with its other numerous benefits.